2019
DOI: 10.1111/jzo.12662
|View full text |Cite
|
Sign up to set email alerts
|

Antiherbivore protection and plant selection by the lynx spider Peucetia flava (Araneae: Oxyopidae) in the Brazilian Cerrado

Abstract: Spiders are ubiquitous in most vegetation, however very little empirical data are available on specific spider–plant interactions and their reciprocal outcomes. In the Brazilian Cerrado, the plant Mimosa setosa var. paludosa, (Fabaceae) has glandular trichomes in its leaves and stems, commonly entrapping insects (i.e. carrion) as well as hosting the lynx spider, Peucetia flava. We hypothesized that: (1) the damage inflicted by exophytic (leaves) and endophytic (seeds) herbivore insects that overcome the glandu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Therefore, greater activity of these protective structures (Calixto et al., 2015) is expected when new plant tissues are produced (i.e. at the beginning of the rainy season; Calixto, Lange, Bronstein, Torezan‐Silingardi, & Del‐Claro, 2020; Calixto et al., 2018; Del‐Claro et al., 2016; Del‐Claro, Stefani, Nahas, & Torezan‐Silingardi, 2017; Sousa‐Lopes, Alves‐da‐Silva, Alves‐Martins, & Del‐Claro, 2019). Seasonal variation in the abundance of ants and herbivores were also related to seasonal climatic conditions of the Brazilian Cerrado (Vilela et al, 2014, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, greater activity of these protective structures (Calixto et al., 2015) is expected when new plant tissues are produced (i.e. at the beginning of the rainy season; Calixto, Lange, Bronstein, Torezan‐Silingardi, & Del‐Claro, 2020; Calixto et al., 2018; Del‐Claro et al., 2016; Del‐Claro, Stefani, Nahas, & Torezan‐Silingardi, 2017; Sousa‐Lopes, Alves‐da‐Silva, Alves‐Martins, & Del‐Claro, 2019). Seasonal variation in the abundance of ants and herbivores were also related to seasonal climatic conditions of the Brazilian Cerrado (Vilela et al, 2014, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, compared to other microhabitats, rosette-shaped plants seem to operate like diversity amplifiers within ecosystems (Gonçalves- Souza et al, 2010;Barrancos et al, 2017). Spiders are widely distributed throughout natural and seminatural ecosystems worldwide (Lessard-therrien et al, 2018;Mestre et al, 2018), and their diversity is highly influenced by habitat complexity and prey availability (Harwood et al, 2003;Sousa-Lopes et al, 2019). Spiders are commonly classified into guilds according to their foraging strategies (Uetz et al, 1999;Cardoso et al, 2011) and each guild interacts differently with rosette-shaped plants.…”
Section: Introductionmentioning
confidence: 99%
“…Glandular trichomes are hair-like structures believed to have evolved as a direct biotic defence against herbivorous insects [ 43 , 44 ]. The insects and carrion (i.e., dead insects) trapped by the glandular hairs represent an energetically cost-free, accessible food source [ 45 ], which attracts arthropod predators, such as spiders, for added protection against herbivory [ 40 , 45 , 46 ]. In three complementary studies, Morais-Filho and Romero [ 39 , 40 , 47 ] observed Peucetia flava exclusively in association with Rhyncanthera dichotoma .…”
Section: Spider–plant Associationsmentioning
confidence: 99%
“…dichotoma fitness (i.e., through predation of pollinators), signifying a potential protective mutualism. Moreover, a recent study by Sousa-Lopes et al [ 45 ] found that the presence of P. flava on the trichome-bearing Mimosa setosa var. paludosa positively correlated with an increase in trapped prey and carrion.…”
Section: Spider–plant Associationsmentioning
confidence: 99%
See 1 more Smart Citation